Rancang Bangun Pengendali Kunci Pintu Berbasis Mikrokontroler Melalui Wireless - Azwardi Azwardi; Meiyi Darlies; Puspitasri Ningtyas (JURNAL INTEGRASI, 2013)
Control system is an important that is often encountered. Controlling at a long distance to take advantage of more advanced technologies such as the computer will make a lot of people get it easier to control syatem. For that invented a device used to control the door locks via wireless microcontroller based. Wireless communication using radio frequency of 27MHz. frequency that is used for remote control and uses Visual Basic 6.0 applications as a control. This device consists of a master module and the slave module. Data sent from the master module form logic 1 or 0. With the number of bits used is 4 bit logic on one instruction. Rated voltage generated at logic 1 is between 3 to 5 volts. While the logic 0 is between 0-1 volt.Data sent in the form of radio wave signal amplitude waves are superimposed with the signal carrier in the form of pulses of radio frequency. When given a logic 1 then the relay contacts are closed, while when given a logic 0 then the relay contact relay will be open. For moving doors, then set the PWM value of its Software. The value of PWM affect the output voltage in a DCmotor.